ROBOTIC AUTOMATION ON COMPUTER NUMERICAL CONTROL MACHINE - Danang Danang; Zaenal Mustofa; Edy Siswanto (Lembaga Pengembangan Kinerja Dosen, 2022)
Along with the advancement of robot technology, Computer Numerical Control (CNC) machine robot automation is becoming more popular. While some Computer Numerical Control engine process independently with a part catcher, a perpendicular granting center requires an extraneous individual to keep the engine processing. Collective and Mechanical robots be the main options for robotize perpendicular Computer Numerical Control grating machines. This study aims to specifically investigate and find the most effective type of robot to be used as a machine capable of maintaining the Haas VF-2 perpendicular crushing center. The method used in this study is the Overal Equipment Effectiveness (OEE) model approach with five different actions, starting with scope, unit setting, evaluation, fee calculation, and integration of the evaluation to present the value of each cell. The purpose of the model used in this study is to determine which robot is more effective for use in industry. As the result, this study demonstrates the important difference between the robot cells on the site and the overall effectiveness of the equipment, besides that the fee differences in the production of robot cells are not too large, but if the focus is on adding robots then the fee differences must be considered carefully. The hazard assessment proved surprising. This study shows that the risk factors in VF-2 treatment using cooperative robots and mechanical robots can be ignored. The impact of takt time also has an important role. Taking each factor into account for the production machining of the VF-2 mechanical robot is more conducive to use because its performance level is almost two times better and in terms of use, it is also much safer. For future work, maintaining a continual level of danger estimate during working on various parts is a very important thing to pay attention to. In addition, when the geometry and materials of machine parts are developed, the collective allocation is no longer valid, so danger estimates must be carried out more carefully to ensure operator safety.